Positional Obstructive Sleep Apnea and Periodic Limb Movements During Sleep: A Large Multicenter Study - Jae Hyun Soh; Yun Jin Kang; Won-Hyuck Yoon; Chan-Soon Park; Hyun-Woo Shin (Clinical and Experimental Otorhinolaryngology, 2024)
Objectives. The relationships among positional obstructive sleep apnea (POSA), obstructive sleep apnea (OSA), and periodic limb movements during sleep (PLMS) remain unclear. We investigated these relationships with respect to the severity of OSA and explored the underlying mechanisms. Methods. We retrospectively reviewed 6,140 eligible participants who underwent full-night diagnostic polysomnography at four clinical centers over a 5-year period, utilizing event-synchronized analysis. We evaluated the periodic limb movement index (PLMI) and the periodic limb movement with arousal index (PLMAI). The impacts of POSA on the PLMI, PLMAI, and PLMS were analyzed in relation to the severity of OSA. Results. The mean PLMI, the mean PLMAI, and the prevalence of PLMS were significantly lower in participants with severe OSA compared to the mild and moderate OSA groups. The mean PLMI among those with mild OSA exceeded that of control participants. Furthermore, the mean PLMI (4.8±12.7 vs. 2.6±9.8 events/hr, P<0.001), the mean PLMAI (0.9±3.7 vs. 0.5±3.3 events/hr, P<0.001), and the prevalence of PLMS (11% vs. 5.3%, P<0.001) were higher in patients with POSA than in those with non-positional OSA. This PLMS finding was particularly pronounced among those with severe OSA (odds ratio [OR], 1.554; 95% confidence interval [CI], 1.065–2.267) and was less evident in the mild (OR, 0.559; 95% CI, 0.303–1.030) and moderate (OR, 1.822; 95% CI, 0.995–3.339) groups. Conclusion. Patients with POSA, especially those with severe OSA, exhibit a comparatively high prevalence of PLMS. In cases involving prominent PLMS, the diagnosis and treatment of POSA and OSA should be considered.